Human Resource ‘Kurikulum Merdeka’ from Design to Implementation in the School: What Worked and What not in Indonesian Education - Yuni Pratikno; Eric Hermawan; Antoni Ludfi Arifin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This articles aims to gain an in-depth knowledge of the human resources of “Kurikulum Merdeka Belajar” design to the implementation capability in the classroom, especially what has been and has not been implemented in the course of Indonesian education. The researchers has obtained several data that have collected from various sources such as book publications, journal publications, and other newspapers that discuss issues of an independent curriculum as well as its implementation and output. The researchers analyzed under a phenomenological approach, a technique where to get a phenomenal answer from a large amount of data to answer the issues of this study. The research used coding the data, evaluating in-depth data, and interpreting the data. Hence, the researchers could draw conclusions that answered the problem validly. The result showed that the human resources in Indonesian, independent from curriculum design to implementation in schools, found significant obstacles where the government was successful in designing the curriculum but it was constrained in implementation. It can be seen quite a lot has been achieved and a lot has not been achieved. Thus these results were helpful for the subsequent study. Keywords: Human Resource, Kurikulum Merdeka, Implementation Kurikulum Merdeka